PROTOTYPE ALAT MONITORING PENCEGAHAN KEBAKARAN PADA RUANG LAB SMK SARASWATI SALATIGA - Barsalinus Milenius Dupat; Rissal Efendi (Media Bina Ilmiah, 2025)
The fire prevention monitoring system for the SMK SARASWATI laboratory in Salatiga City is a crucial aspect of ensuring that fire disasters do not occur in the laboratory. This is due to the presence of materials and equipment within the laboratory that have the potential to trigger fires. Preventive measures such as installing fire extinguishers, storing flammable chemicals away from heat sources, organizing electrical installations, and enforcing a no-smoking policy have been implemented. However, the existing system is not equipped with automated remote monitoring technology for real-time supervision. With current technological advancements, particularly in the Internet of Things (IoT) systems, the author designed a laboratory room monitoring system at SMK SARASWATI that can monitor temperature, humidity, and air quality in real-time. The system is designed to provide automatic notifications to mobile devices via the user's smartphone, enhancing efficiency in addressing potential fire risks. This technology utilizes the Blynk application and the ESP8266 microcontroller, along with temperature, humidity, and air quality sensors to read environmental conditions. The data collected by the sensors is transmitted via the internet to the Blynk application on the smartphone, enabling 24/7 monitoring without distance limitations. The implementation of this system is expected to prevent fires in the laboratory effectively.